Model Law on Post Morten Inquest - Paipadist, Wasinrapee; Chokmoh, Poom; Sarnnoi, Egkapong (Journal of Humanities and Social Sciences Loei Rajabhat University, 2024)
The research on Model Law On Post Mortem Inquest aimed (1) to study the problem status of a post-mortem inquest in Thailand, (2) to conduct a comparative study between Thai post-mortem inquest and overseas post-mortem inquest, (3) to draft a law on Thai post-mortem inquest, and (4) to evaluate the draft law on Thai post-mortem inquest. The research was conducted based on a qualitative research design, consisting of documentary research, an in-depth interview, and focus group discussion. The research results revealed that there were legal and practical problems in Thai post-mortem inquest, i.e. problems related to the post-mortem inquest system, problems related to standards of the organizations responsible for performing a post-mortem inquest, problems related to determining the ground for performing a post-mortem inquest, problems related to the procedures required for conducting a post-mortem inquest, problems related to performing check and balance, and problems related to the use of officials’ discretion. In order to solve the problems related to a post-mortem inquest, which is a way to protect people’s rights and to improve the justice system, this research adopted a guideline from the analysis to design a model law on post-mortem inquest. The structure of the law consisted of general provision, the committee on post-mortem inquest, officers, office and the scope of authority, a post-mortem inquest, and penalty. The research suggested that the model law on post-mortem inquest should be enacted to be a law in accordance with the legislative process for enforcement.